Profiling safety of intravitreal injections for retinoblastoma using an anti-reflux procedure and sterilisation of the needle track. Issue 8 (24th February 2012) - Munier, Francis L; Soliman, Sameh; Moulin, Alexandre P; Gaillard, Marie-Claire; Balmer, Aubin; Beck-Popovic, Maja
Abstract : Background: The preservation of globe integrity has always been a major concern during the treatment of retinoblastoma for fear of extraocular or metastatic spread. Intravitreal chemotherapy has been attempted as a desperate salvage therapy only for eyes with refractory retinoblastoma. Published data on the safety and efficacy of this route are, however, limited. Methods: A modified technique of intravitreal injection in eyes with retinoblastoma is described. All children with retinoblastoma who received one or more intravitreal injections using this technique were retrospectively reviewed concerning ocular complications of the injection procedure as well as clinical or histopathological evidence of tumour spread. Results: 30 eyes of 30 children with retinoblastoma received a total of 135 intravitreal injections, with a median follw-up duration of 13.5 months. No extraocular spread was seen on clinical follow-up in any patients and there was no tumour contamination of the retrieved entry sites histopathologically analysed among the five enucleated eyes. No significant ocular side effects were observed except transient localised vitreous haemorrhage (3/135). Conclusion: This technique is potentially safe and effective at a low cost and may play a promising role, especially in the treatment of recurrent and/or resistant vitreous disease in retinoblastoma, as an alternative to enucleation and/or external beam radiotherapy. However, this treatment should not replace the primary standard of care of retinoblastoma and should not be considered in group E eyes. Its application should be approved by an ophthalmological-oncological team and it should be performed by an experienced eye surgeon in a tertiary referral centre after careful selection of a tumour-free injection site.